Avaliação da susceptibilidade do primata Cebus apella (Primates: Cebidae) à infecção experimental com diferentes inóculos de Leishmania (Leishmania) chagasi - SANTOS, Dirceu Costa dos (Universidade Federal do Pará, 2013)
In Brazil, the monkey Cebus apella has been successfully used as a model for studying cutaneous leishmaniasis. Thus, we decided to investigate its usefulness as a model for visceral leishmaniasis. For this purpose, we used 10 specimens of C. apella: 7 males and 3 females, juveniles. All were born and raised in captivity. In the first experiment was realize with 6 monkeys divided in 2 groups, in the first group with 3 monkeys was inoculated with 30 x 106 promastigotes of L. (L.) chagasi (MCAO/BR/1998/M18011, Maranhão State) from stationary phase of cultures, while in the second group with 3 monkeys was inoculated 5 doses successive with 30 x 106 promastigotes (150 x 106) of L. (L.) chagasi (MCAO/BR/1998/M18011, Maranhão State) from stationary phase of cultures. In the second experiment were used 4 monkeys, divided in 2 groups was also inoculated with five pairs of salivary glands of Lutzomyia longipalps together with parasites. In the first group with 2 monkeys was inoculated with 30 x 106 promastigotes of L. (L.) chagasi, second group with 2 monkeys was inoculated 5 doses successive with 30 x 106 promastigotes (150 x 106). The inoculations were, intradermaly, into the base of the tail of the animals. The evaluation of infections was monthly and included clinical examination, IgG antibody response (IFAT). In monkeys inoculated with promastigotes only or in those inoculated with promastigotes plus the salivary glands of the flebotominae sand fly we have till now found no clinical manifestations of infection all the experiment, neither have demonstrated parasites in the bone-marrow or specific antibody response. These results suggest that C. apella monkey is able to resist against to infection by L. (L.) chagasi.